Description of fluid-tethered chains interfaces: advances in density functional theories and off-lattice computer simulations - Sokołowski, S.; Ilnytskyi, Ja.; Pizio, O. (Condensed Matter Physics, 2014)
Many objects of nanoscopic dimensions involve fluid-tethered chains interfaces. These systems are of interest for basic science and several applications, in particular for design of nanodevices for specific purposes. We review recent developments of theoretical methods in this area of research and in particular of density functional (DF) approaches, which provide important insights into microscopic properties of such interfaces. The theories allow to describe dependence of adsorption, wettability, solvation forces and electric interfacial phenomena on thermodynamic states and on characteristics of tethered chains. Computer simulations for the problems in question are overviewed as well. Theoretical results are discussed in relation to simulation results and some experimental observations.